The role of news media in framing anti-Coptic attacks and Muslim-Coptic relations in Egypt: A frame analysis - Mahfouz, Esraa Fayez (AUC Knowledge Fountain, 2018)
This study aims at examining the different frames used by the governmental newspaper â€œAl Ahramâ€ and the independent newspaper â€œAl Masry Elyoumâ€ in covering anti-Coptic attacks in Egypt from 2011 till 2017, under two different ruling regimes. The researcher conducted a content analysis of 553 news stories that were published a week after each attack. The researcher aimed at exploring the different frames used by each newspaper, whether those frames have varied along the different ruling periods, or across different newspaper ownership. The study has also examined the frame context used by newspapers to frame the attacks and the dominant news sources attributed by journalists in the coverage of the attacks. The study has further examined how the different news sources affected the type of frame, and finally the impact of different ruling periods on the attribution of blame. The results have shown that both newspapers relied mostly on the morality frame in their portrayal of the attacks. The results have further indicated that the use of some frames like the morality frame, the conflict frame and the economic consequences frame have not differed across both newspapers. The first has been the mostly used and the latter has been the least used. However, the attribution of responsibility frame has been used more by the independent newspaper, while the war on terror frame has been used more by the governmental newspaper. The use of frames have also differed across different ruling periods. For instance, under Mubarakâ€™s regime, the attacks were framed using the morality frame; while under Sisiâ€™s regime, the attacks were framed using the war on terror frame. The results have also shown that the overall frame context in the press coverage of the anti-Coptic attacks has been the thematic frame. Previous research has indicated an increase in the use of official sources, since they are perceived as the most credible sources. The findings of the study support those findings, since official sources have dominated more than half the coverage. The research has further indicated that some sources played a significant role in framing anti-Coptic attacks. As for the attribution of blame, the findings suggest that under Mubarakâ€™s ruling period, the blame was mainly on foreign agents, while under Sisiâ€™s ruling period, the blame was pointed at terrorists.